STUDY OF LEACHING BEHAVIOR OF RARE EARTH ELEMENTS FROM SISODING GRANITE WEATHERED SOIL, NORTH SUMATRA IN HYDROCHLORIC ACID - M. Al Wafi, T.
Rare earth elements (REE) have many uses in advanced technology. One of the ores that are widely used to extract REE is the ion-adsorption clay type from weathered granite soil. Currently, the production and market of REE are still dominated by several countries such as China and the United States. In Indonesia, there are several areas with REE potential, one of which is in the Sisoding area, North Sumatra Province. In this study, the extraction process of REE from weathered granite soil originating from the Sisoding area was studied, which has ion-adsorption clay type. The extraction process is carried out by leaching in a solution of ammonium sulfate and a solution of hydrochloric acid.